Effects of ageing on myenteric neuronal number and neuromuscular function in the human colon. (25th February 2016) - Kung, Victor; Broad, John; Carroll, Rebecca; Knowles, Charles; Sanger, Gareth
Abstract: Background: Degeneration of cholinergic neurons (with sparing of nitrergic nerves) has been described in the enteric nervous system of ageing animals, and proposed to contribute to chronic constipation in older people. We hypothesise that enteric neurodegeneration also occurs in people. This study aimed to investigate whether neuronal loss in myenteric plexus and altered neuromuscular function occur in the human ascending and descending colon with advanced ageing. Methods: Macroscopically normal ascending and descending colons were obtained from patients aged ≥70 years and ≤60 years undergoing non-obstructed bowel cancer surgery. 4 μm tissue sections were stained with HuC/D antibodies. Two masked observers independently quantified numbers of myenteric ganglia and neurons. Neuromuscular functions of circular muscle strips were examined by stimulating intrinsic nerves using 1–20 Hz electrical field stimulation (EFS) in tissue baths. Muscle acetylcholinesterase activities were analysed by colorimetric assays. Data are expressed as median (IQR) and compared by Mann-Whitney U test. The study was approved by research ethics committee and written informed consent was obtained from patients. Findings: Myenteric ganglia and nerve counts were performed in 40 patients (22 men, 18 women, ten for each region and age group). The two age groups had no significant differences in numbers of HuCD+ ganglia and nerves in both colon regions. 5 Hz EFS-evoked responses were studied in circular strips from 164 patients (ascending colon 52 patients aged ≥70 years, 28 aged ≤60 years; descending colon 40 and 44, respectively). EFS-evoked neuronally mediated contraction or relaxation, usually followed by an after-contraction on termination of the stimulus. In each patient, not all strips showed the same movement response to EFS, with contraction in some and relaxation in others. A median of eight strips (IQR 6–13) were therefore examined per patient and the proportion of strips that relaxed was determined. In ascending colon, EFS was significantly more likely to evoke relaxation if a patient was aged 70 or more than if 60 or younger (32% [18–67] vs 20% [3–43], p=0·05), a change not observed in descending colon. Cholinergic contractions (measured in five patients in each age group) evoked by 1–20 Hz EFS during nitrergic inhibition (with L-NAME) were also reduced for patients in the ≥70 year age group in ascending colon only (p=0·04 across 1–20Hz, two-way ANOVA—eg, at 5 Hz 2·0 g tension generated by EFS/g tissue weight [1·6–2·6] vs 4·6 [1·4–12·2]). No significant differences were observed in acetylcholinesterase activities in either age group (ten patients in each). Direct muscle contraction by 1 nM–100 μM carbachol (ten aged ≥70 years, eight ≤60 years) and relaxation by 10 nM–1 mM nitroprusside (12 aged ≥70 years, five ≤60 years) were unchanged. Interpretation: No overall loss of myenteric ganglia and neurons was observed in the human colon with advanced ageing. However, neuromuscular function in the ascending colon appeared to be altered, potentially because of impaired cholinergic neuronal functions. The study is limited by a lack of cholinergic and nitrergic nerve counts (which is ongoing); strengths are objective myenteric quantifications by two independent raters and its large survey on colonic neuromuscular functions. Funding: Age UK, Dunhill Medical Trust, Barts and The London Charity, Bowel & Cancer Research.